2021
DOI: 10.1080/23311975.2021.1885573
|View full text |Cite
|
Sign up to set email alerts
|

Working from home during the corona pandemic: Investigating the role of authentic leadership, psychological capital, and gender on employee performance

Abstract: The Corona Pandemic has forced many organizations to limit human interactions by implementing what so-called Work-from-Home (WFH). This study aims to investigate the role of Authentic Leadership, Psychological Capital, and employees' gender in predicting employees' performance in a public organization in Indonesia during the implementation of WFH. Participants were recruited from a governmental institution under the Minister of Home Affairs in Indonesia. An online survey link was sent to 150 full-time employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 61 publications
4
63
0
1
Order By: Relevance
“…The service sector faced complete closure because of direct human contact and the rules of social distancing [7], especially tourism, health, media and entertainment, and transport industries [8]. In these sectors, employees are at more risk of contracting coronavirus because they have to interact with customers directly and come in direct or indirect contact with many customers, or they must manage items used or touched by the consumers [9]. Along with this fear of the virus, employees of different sectors faced various issues related to reduced salary or job loss.…”
Section: Introductionmentioning
confidence: 99%
“…The service sector faced complete closure because of direct human contact and the rules of social distancing [7], especially tourism, health, media and entertainment, and transport industries [8]. In these sectors, employees are at more risk of contracting coronavirus because they have to interact with customers directly and come in direct or indirect contact with many customers, or they must manage items used or touched by the consumers [9]. Along with this fear of the virus, employees of different sectors faced various issues related to reduced salary or job loss.…”
Section: Introductionmentioning
confidence: 99%
“…During the early stages of the pandemic, Daraba et al (2021) found that employees needed support from their leaders to secure and restore their psychological resources. Typical for the early stages of the COVID-19 pandemic was that many employees and their managers had to work from home (WFH), and according to Daraba et al (2021) working from home brought changes to employee's work life, including how they perceived leadership.…”
Section: Leaders' Ability To Changementioning
confidence: 99%
“…During the early stages of the pandemic, Daraba et al (2021) found that employees needed support from their leaders to secure and restore their psychological resources. Typical for the early stages of the COVID-19 pandemic was that many employees and their managers had to work from home (WFH), and according to Daraba et al (2021) working from home brought changes to employee's work life, including how they perceived leadership. For those who previously did not work from home, this was a change of organizational context, where the interactions between leaders and followers become different as tasks and interactions were performed digitally (Daraba et al 2021).…”
Section: Leaders' Ability To Changementioning
confidence: 99%
See 1 more Smart Citation
“…Governance in the field of facilities and infrastructure Governance in the field of facilities and infrastructure is very urgent in supporting the implementation of an effective learning process (Daraba et al, 2019;Cahaya et al, 2019;Daraba et al, 2021Daraba et al, , 2018. The arrangement of facilities and infrastructure must be carried out optimally so that later it will create a safe, orderly, beautiful, and comfortable atmosphere.…”
Section: School Operationsmentioning
confidence: 99%